Application of the CometChip platform to assess DNA damage in field‐collected blood samples from turtles. (14th March 2018) - Sykora, Peter; Chiari, Ylenia; Heaton, Andrew; Moreno, Nickolas; Glaberman, Scott; Sobol, Robert W.
Abstract : DNA damage has been linked to genomic instability and the progressive breakdown of cellular and organismal homeostasis, leading to the onset of disease and reduced longevity. Insults to DNA from endogenous sources include base deamination, base hydrolysis, base alkylation, and metabolism‐induced oxidative damage that can lead to single‐strand and double‐strand DNA breaks. Alternatively, exposure to environmental pollutants, radiation or ultra‐violet light, can also contribute to exogenously derived DNA damage. We previously validated a novel, high through‐put approach to measure levels of DNA damage in cultured mammalian cells. This new CometChip Platform builds on the classical single cell gel electrophoresis or comet methodology used extensively in environmental toxicology and molecular biology. We asked whether the CometChip Platform could be used to measure DNA damage in samples derived from environmental field studies. To this end, we determined that nucleated erythrocytes from multiple species of turtle could be successfully evaluated in the CometChip Platform to quantify levels of DNA damage. In total, we compared levels of DNA damage in 40 animals from two species: the box turtle ( Terrapene carolina ) and the red‐eared slider ( Trachemys scripta elegans ). Endogenous levels of DNA damage were identical between the two species, yet we did discover some sex‐linked differences and changes in DNA damage accumulation. Based on these results, we confirm that the CometChip Platform allows for the measurement of DNA damage in a large number of samples quickly and accurately, and is particularly adaptable to environmental studies using field‐collected samples. Environ. Mol. Mutagen. 59:322–333, 2018. © 2018 Wiley Periodicals, Inc.